An outbreak of strangles associated with a novel genotype of Streptococcus equi subspecies equi in donkeys in China during 2018. (10th April 2019) - Dong, J.; Gao, N.; Waller, A. S.; Cook, F. R.; Fan, S.; Yuan, D.; Du, Y.; Li, F.; Norimine, J.; Zhu, W.
Summary: Background: Strangles is a highly contagious respiratory disease of equids caused by the bacterium Streptococcus equi subspecies equi . Objectives: To identify the cause of an outbreak of strangles that occurred on donkey farms within the Shandong Province of China and determine the prevalence of the disease. Study design: Cross‐sectional. Methods: Samples were taken from clinically affected animals to measure the prevalence of strangles within the population of donkeys at six intensive farms in China and identify the SeM type of isolate recovered from affected animals. Diagnosis was confirmed by bacterial isolation, biochemical tests and PCR. Epidemiological data were analysed using Chi‐square test and a Fisher's exact two‐sided test. The SeM gene of S. equi isolates recovered from affected animals was determined and compared with the SeM database PubMLST‐seM. Results: In July and August 2018, an outbreak of strangles occurred on six donkey farms within the Shandong Province of China. The overall prevalence of disease within the different donkey herds was 13.4%. Younger animals were worst affected with 40.3% (83/206) of donkey foals aged under 1 year exhibiting clinical signs compared with 12.5% (191/1525) of donkeys aged one to 2 years and 3.8% (17/442) of donkeys over 2 years of age. Analysis of SeM sequencing data identified that the farms were affected by the same strain of S .  equi, SD201807, which contains the novel 136 allele of SeM. Main limitations: Healthy donkeys were not sampled in this study. Conclusions: The number of intensive donkey breeding farms in China has risen recently. The higher numbers of animals that are in closer proximity to one another raise the potential for the transmission of infectious diseases such as strangles. This is the first description of a strangles outbreak among donkey herds in China. The Summary is available in Chinese – see Supporting information.